Accounting and finance for non-specialists - Atrill, Peter; McLaney, E. J. (Harlow Pearson, 2022)
"This book provides an introduction to accounting and finance. It is aimed at Students who are not majoring in accounting or finance but who are, nevertheless, studying introductory level accounting and finance as part of their course. The course may be in business, economics, hospitality management, tourism, engineering or some other area. For these students, the book provides an overview of the role and usefulness of accounting and finance within a business or some other organisation. Students, who are majoring in either accounting or finance. These students should find the book a helpful introduction to the main principles, which can serve as a foundation for further study"--
Revised edition of the authors' Accounting and finance for non-specialists, [2019]
Includes bibliographical references and index.
Keywords: Accounting; Financial statements